1980
DOI: 10.1002/jbm.820140413
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of human α‐thrombin with artificial surfaces and reactivity of adsorbed α‐thrombin

Abstract: Thrombin adsorbed onto Cuprophane or poly(vinyl chloride) (PVC) was shown to be inactive with respect to amidase activity. Desorbed thrombin from these two artificial surfaces showed only low amidase activity. However, in the presence of albumin, the surface‐bound thrombin appeared to exhibit increased amidase activity. This apparent activity may be due to the action of thrombin displaced from the surfaces by albumin. Thrombin bound to Cuprophane or PVC was shown to be capable of reacting with antithrombin III… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…The surfaces of 16 different polymers were characterized using static secondary ion mass spectroscopy, electron spectroscopy for chemical analysis, and contact angle measurements of several liquids. This study found a high degree of positive correlation between fibrinogen binding and a high dispersive component of surface energy was also observed to correlate with fibrinogen retention at the material surface, indicating stronger interactions (6). The results of our study suggest that 3M and Carmeda heparin-coated PVC tubings may offer the most biocompatible luminal surface with the least amount of fibrinogen binding and retention.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The surfaces of 16 different polymers were characterized using static secondary ion mass spectroscopy, electron spectroscopy for chemical analysis, and contact angle measurements of several liquids. This study found a high degree of positive correlation between fibrinogen binding and a high dispersive component of surface energy was also observed to correlate with fibrinogen retention at the material surface, indicating stronger interactions (6). The results of our study suggest that 3M and Carmeda heparin-coated PVC tubings may offer the most biocompatible luminal surface with the least amount of fibrinogen binding and retention.…”
Section: Discussionsupporting
confidence: 63%
“…Every different type of synthetic material will have a characteristically different layer of adsorbed proteins at the blood-material interface. Studies have shown a clear correlation between the hydrophobicity of synthetic surfaces an their ability to bind and retain fibrinogen (6). Numerous studies have shown that fibrinogen is a primary component of the adsorbed protein layer (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…On some surfaces, like polymers [14,15], thrombin loses almost all of its catalytic activity. On glass Mizutani observed that activities increased [16].…”
Section: Introductionmentioning
confidence: 99%
“…No significant difference was observed between the blood test performed two points before occlusion and that performed before occlusion for ALB (Figure 6 ), although a trend towards a decrease at all calcium injection flow rate groups was observed. This is likely attributed to an adsorption reaction of ALB on polyvinyl chloride, which is used in blood circuits and seat bags [ 20 , 21 ]. Additionally, polyvinyl chloride transports small amounts of CO 2 gas [ 22 - 23 ], which might have affected the pH of the blood, leading to charge changes and ALB measurement errors.…”
Section: Discussionmentioning
confidence: 99%